When normal scores don't equate to independence: Recalibrating ratings of neurobehavioural disability from the 'St Andrew's – Swansea Neurobehavioural Outcome Scale' to reflect context-dependent support. (28th January 2018) - Alderman, Nick; Williams, Claire; Wood, Rodger Ll.
ABSTRACT: Primary objective : Context is critical to the interpretation of measurement instruments that capture acquired brain injury (ABI) outcomes. Ratings reflect behaviours and abilities observed in a particular setting; it cannot be assumed that results are generalizable beyond these. This study explored the utility of a method to convey the impact of context-dependent support given on ratings of neurobehavioural disability (NBD) using the St Andrews-Swansea Neurobehavioural Outcome Scale (SASNOS). Methods and procedures : A supplementary SASNOS scoring system was developed using a mixed-methods approach. Dependency ratings were used to recalibrate standardised SASNOS scores to reflect support received. To aid interpretation, an expert panel reviewed SASNOS ratings for 50 ABI cases participating in residential neurobehavioural rehabilitation programmes. An end-user survey was undertaken to explore some of its psychometric properties. Finally, a representative case study was employed to illustrate its clinical utility. Main outcomes : The expert panel identified three dependency profiles: (1) Normal/Independent ; (2) Normal/Dependent ; and (3) Abnormal/Review . Survey results supported face and construct validity of the supplementary system; the case study demonstrated benefits of discriminating between dependency profiles. Conclusions : The supplementary scoring system enables SASNOS to convey the impact of support received on ratings of NBD, solidifying its usefulness for measuring outcomes in rehabilitation.